Morphological and molecular characters of Cherax quadricarinatus (von Martens, 1868) from Sermo Reservoir and Tambakboyo Retention Basin, Daerah Istimewa Yogyakarta, Indonesia - Rury Eprilurahman; Aplina Krismutia Simarmata; Lukman Hakim; Trijoko Trijoko (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2021)
The Australian red claw freshwater crayfish, Cherax quadricarinatus is one of the most widely distributed and cultivated freshwater crayfish due to its high tolerance towards various environmental conditions. Native to North Australia and South Papua New Guinea, this crayfish was found in Tambakboyo Retention Basin in 2016 and Sermo Reservoir in 2019. This research was aimed to identify the morphological and molecular characters of C. quadricarinatus collected from Sermo Reservoir and Tambakboyo Retention Basin, Yogyakarta. The genetic information of the samples was compared to Australian red claw freshwater crayfish currently available. The methodology used for this research are morphological, morphometrical, meristic identification, and molecular identification using the PCR method. The primer used to be 1471 primers as the forward primer and 1472 primers as the reverse primer. In conclusion, all six specimens obtained were identified to be C. quadricarinatus. Morphological analysis using UPGMA showed that all specimens were formed one big cluster and has the highest similarity index (1.00). Molecular analysis using BLAST showed that specimen from Sermo Reservoir was 98.96% identical to C. quadricarinatus and specimen from Tambakboyo Retention Basin was 100% identical to C. quadricarinatus. Thus concluding that based on their morphological and molecular character, all samples of this study were C. quadricarinatus. This finding also contributes to the distribution information of C. quadricarinatus in Daerah Istimewa Yogyakarta